Mechanical Ventilation Management in COVID-19 Patients - Wibowo; Frischa; Harjanto; Bernadus Realino Realino (Cermin Dunia Kedokteran, 2022)
Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2), was first reported in Wuhan, Hubei, China, and has spread to more than 200 other countries around the world. COVID-19 can be complicated by severe pneumonia, ARDS, sepsis, and septic shock in severe cases. About 80% of cases are mild or moderate, 13.8% have severe disease, and 6.1% fall into a critical condition. Positive responses in COVID-19 patients with respiratory failure are usually seen right after the initiation of NIV and HFNC. If there is no substantial improvement in gas exchange and respiratory rate within a few hours, invasive mechanical ventilation should be started without delay. Delayed intubation increases COVID-19 ARDS mortality. Coronavirus disease 2019 (COVID-19), yang disebabkan oleh Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2), pertama kali dilaporkan di Wuhan, Hubei, China, dan telah menyebar ke lebih dari 200 negara lain di seluruh dunia. Manifestasi klinis pasien COVID-19 sebagian besar tidak bergejala (asimtomatik), namun dapat diperumit dengan pneumonia berat, ARDS, sepsis, hingga syok septik. Sekitar 80% kasus biasanya ringan atau sedang, 13,8% mengalami gejala berat, dan 6,1% pasien mengalami kondisi kritis. Respons positif biasanya terlihat segera setelah dimulainya NIV dan HFNC. Jika tidak ada perbaikan substansial dalam pertukaran gas dan laju pernapasan dalam beberapa jam, ventilasi mekanik invasif harus dimulai segera. Intubasi yang tertunda meningkatkan mortalitas ARDS.